PENGARUH PENILAIAN KINERJA DAN MOTIVASI KERJA GURU TERHADAP PRODUKTIVITAS PENDIDIKAN DI SD NEGERI GUGUS VI KECAMATAN SUNGAITARAB - Lastri Efida (IAIN Batusangkar, 2016)
This research was aimed at finding the influence of teachers’ work assessment toward teachers’ productivity; the influence of teachers’ work motivation toward teachers’ productivity, and the correlation between teachers’ work assessment and teachers’ work motivation toward teachers’ productivity. This research was correlational research with quantitative method. Population in this research were headmaster and teachers in State Primary School Gugus VI Sungaitarab, there were about 48 peoples. Research data were collected by using questionnaire with likert scale model and were analyzed by using correlational analysis technique and regretion analysis technique by utilizing SPSS. 18 application. The analysis of respondent’s acceptance level showed that the teachers’ work assessment have a correlation toward teachers’ productivity as 85,36% with 0,829 correlation score as first hypothesis. Teachers’ work motivation have a correlation toward teachers’ productivity as 52,7% with 0,50 correlation score as second hypothesis. Teachers’ works assessment and teachers’ work motivation have correlation toward teachers’ productivity as 82,23% respondent’s acceptance level with 00,1 correlation score as third hypothesis.Keyword: Teachers’ Work Assessment, Teachers’ Work Motivation, Teachers’ Productivity, State Primary School Gugus VI Sungaitarab.